HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP MALARIA DENGAN KEPATUHAN PEMAKAIAN KELAMBU DI KABUPATEN MUARA ENIM - DSP, I Gede Wempi; Hapsari, Nungki; Ritawati, Ritawati (Publikasi Penelitian Terapan dan Kebijakan, 2014)
The use of insecticide-treated nets is one of the malaria control efforts. Efforts to reduce malaria with mosquito nets API will get higher results, when supported public participation to obey in the use of mosquito nets. This study aims to determine the relationship between knowledge and attitudes towards malaria with mosquito net usage compliance. This research is a descriptive cross sectional study was done in the village of Tegal rejo, village of Darmo and hamlet of Muara Enim, Lawang Kidul and Muara Enim District of Muara Enim regency in May until November 2012. Based on the analysis using the chi-square statistic indicates that there is a significant relationship between attitudes towards malaria with mosquito net usage adherence (p<0.05). As for the knowledge society against malaria no significant association with the use of mosquito nets adherence (p>0.05). Thus the extension needs to be focused on malaria knowledge and benefits of the use of mosquito nets and how to treat them so that people know the importance of using bed nets for malaria prevention.